GE_GERICHTE P/859/2014 vom 14. September 2015 - GE Cour de justice (2015)
IN DUBIO PRO REO; COAUTEUR(DROIT PÉNAL); ASSISTANCE JUDICIAIRE; VOL(DROIT PÉNAL) | CP.139; CP.172ter; CP.140.1; CP.186; CP.47; CP.49; CP.52; CPP.135